2012
DOI: 10.1124/dmd.112.048561
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual and Interindividual Variabilities in Endogenous Cortisol 6β-Hydroxylation Clearance as an Index for In Vivo CYP3A Phenotyping in Humans

Abstract: This study was designed to evaluate the in vivo activity of cytochrome P450 3A (CYP3A) in 49 healthy Japanese subjects aged 22-58 years using endogenous cortisol 6b-hydroxylation clearance [CLm(6b)], a novel biomarker for CYP3A phenotyping. CLm(6b) in the 49 healthy subjects was 2.40 6 0.79 ml/min with an approximately 4-fold interindividual variability of CYP3A activity. The mean clearance in the 24 women was 2.50 6 0.89 ml/min; the value in the women was higher than in the 25 men (2.30 6 0.69 ml/min) by appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
(36 reference statements)
0
17
1
Order By: Relevance
“…24 A recent study reported an approximately fourfold interindividual variability of CYP3A activity using the 6b-hydroxylation clearance and the within-day intra-individual clearance variability was relatively small with no characteristic diurnal rhythms observed. 36,37 This differs from previous findings from our group using the urinary 6b-OHF/F ratio where the interindividual variability showed a 30-fold difference 38 and there was a significant diurnal variation. 25…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…24 A recent study reported an approximately fourfold interindividual variability of CYP3A activity using the 6b-hydroxylation clearance and the within-day intra-individual clearance variability was relatively small with no characteristic diurnal rhythms observed. 36,37 This differs from previous findings from our group using the urinary 6b-OHF/F ratio where the interindividual variability showed a 30-fold difference 38 and there was a significant diurnal variation. 25…”
Section: Discussioncontrasting
confidence: 99%
“…It was suggested that endogenous 6β‐hydroxylation clearance calculated from the amount of urinary 6β‐OHF excreted divided by the AUC of plasma F was a better marker than the ratio and was able to show the inhibitory effects of clarithromycin on the in vivo CYP3A activity whereas the urinary 6β‐OHF/F ratio could not . A recent study reported an approximately fourfold interindividual variability of CYP3A activity using the 6β‐hydroxylation clearance and the within‐day intra‐individual clearance variability was relatively small with no characteristic diurnal rhythms observed . This differs from previous findings from our group using the urinary 6β‐OHF/F ratio where the interindividual variability showed a 30‐fold difference and there was a significant diurnal variation …”
Section: Discussionmentioning
confidence: 98%
“…The expression of cytochrome P450 (CYP) 3A7 at birth declines during the first 6 months of life because of the presence of unstable CYP450 polymorphisms in children, together with individual variability, whereas CYP3A4 reaches adult levels after 1 year of age . Moreover, serial intraindividual and interindividual variabilities of CYP3A activity have been reported . On the basis of the lower rate of rejection, the tendency for an increased rate of infection, and the higher conversion rate in younger infants, the therapeutic immunosuppression levels and the type of immunosuppressant should be tailored for individual infants, especially in patients who require LDLT during the first 3 months of life.…”
Section: Discussionmentioning
confidence: 99%
“…(30,31) Moreover, serial intraindividual and interindividual variabilities of CYP3A activity have been reported. (32) On the basis of the lower rate of rejection, the tendency for an increased rate of infection, and the higher conversion rate in younger infants, the therapeutic immunosuppression levels and the type of immunosuppressant should be tailored for individual infants, especially in patients who require LDLT during the first 3 months of life.…”
Section: Discussionmentioning
confidence: 99%
“…5,6) In general, the assessment of in vivo CYP activity is performed by administration of a selective probe for the target enzyme and the subsequent determination of the appropriate pharmacokinetic parameters, or by using the metabolism of endogenous substrates. 7,8) Above all, breath tests, where a 13 C-or 14 C-labeled drug is administered as a probe followed by measurement of the labeled CO 2 in expiration, are advantageous in that the procedures are simple and convenient, particularly in clinical settings. Although such breath tests have been studied for various CYP isoforms, 9) a breath test for CYP3A4 is of great value because the isoform is the most abundant and versatile.…”
mentioning
confidence: 99%